To use or not to use? an ethical analysis of access to data and samples of a deceased patient for genetic diagnostic and research purposes - Mahshad Noroozi; Fatemeh Bahmani; Kazem Mousavizadeh; Saeedeh Saeedi Tehrani; Akram Hashemi; Mina Forouzandeh (Journal of Medical Ethics and History of Medicine, 2022)
Using genetic tests on deceased patients’ samples for diagnostic purposes affects the family members' health and lives but raises some ethical issues in today’s practice of medicine and research. In this paper, we address a common ethical dilemma of clinicians regarding whether to perform genetic tests on a deceased patient’s sample upon a request from first-degree relatives against the patient's wishes in the last days of life. In this paper, a real case scenario is presented that echoes the above-mentioned ethical challenge. Reviewing the genetic basis of the case, the ethical arguments for and against the reuse of genetic material in a clinical context are discussed. An ethico-legal analysis of the case is proposed based on Islamic medical ethics resources. As reusing stored samples of expired patients without their consent also challenges the researchers in the field of genetics, a debate is included on the post-mortem use of genetic data and samples for research.Finally, defining the special features of the presented case and positive benefit-risk ratio, it is concluded that reusing the patient's sample may be justified if the first-degree family members insist on genetic testing and are comprehensively informed about the benefits and harms.